2021
DOI: 10.4046/trd.2020.0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particulate Matter 10 Inhalation on Lung Tissue RNA expression in a Murine Model

Abstract: Background: Particulate matter 10 (PM 10 ; airborne particles <10 μm) has been demonstrated to induce airway and lung diseases. We aimed to investigate the effects of PM 10 on RNA expression in lung using a murine model. Methods: Female BALB/c mice were treated with PM 10 , ovalbumin (OVA), or both (OVA/ PM 10). PM 10 was intranasally administered four times over 2 weeks, and OVA was intraperitoneally injected and then intranasally administered. After 2 days from the last challenges, mice were sacrificed. Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…SNORD15B is a C/D box snoRNA encoded in ribosomal protein S3 gene [ 19 ], SNORA5C is a H/ACA box snoRNA encoded in lncRNA SLERT and it is required for SLERT lncRNA biogenesis and nucleolar translocation [ 16 ]. Snord15b can be induced by particulate matter 10 (PM10) causing airway inflammation and lung fibrosis in BALB/c mice [ 21 ]. And it is upregulated in human CRC tissues in the metastasis versus the benign group according to Koduru et al's research [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNORD15B is a C/D box snoRNA encoded in ribosomal protein S3 gene [ 19 ], SNORA5C is a H/ACA box snoRNA encoded in lncRNA SLERT and it is required for SLERT lncRNA biogenesis and nucleolar translocation [ 16 ]. Snord15b can be induced by particulate matter 10 (PM10) causing airway inflammation and lung fibrosis in BALB/c mice [ 21 ]. And it is upregulated in human CRC tissues in the metastasis versus the benign group according to Koduru et al's research [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The “adenoma-carcinoma sequence” is generally recognized in pathological process of CRC, approximately 15% of colorectal nonmalignant adenomas (also called polyps) are expected to be developed to the carcinoma within about ten years [ 24 ]. According to Han et al's report, Snord15b responses to PM10 caused lung inflammation in mouse model [ 21 ]. Via analyzing the correlation between expression of SNORD15B/SNORA5C and clinicopathological parameters of CRC patient cohorts, we noted that both SNORD15B and SNORA5C were significantly associated with history of colon polyps, which is usually caused by chronic inflammation in colorectum.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression of FCGBP and MUC5AC increases significantly, by approximately 58-fold, when the animals of an ovalbumin-induced asthma mouse model are exposed to PM10 (43). FCGBP produced by bronchial mucus gland cells and goblet cells in children may be involved in the unique Ab response, recurrent infection, and the effects of serum therapy and vaccination (15).…”
Section: Role Of Iggfc-binding Protein In Mucosal Defensesmentioning
confidence: 99%
“…Bertero et al (Bertero et al, 2018) rst pointed out that activated phosphorylated Smad2/3 can enter the nucleus and bind to RNA methyltransferase complex, then induces m 6 A RNA methylation in pluripotent stem cells. Some toxicological studies have pointed out that PM exposure can induce an increase in TGFβ expression (Han et al, 2021;Kyung et al, 2012), which resulted in pulmonary brosis. TGF-β-Smad has been identi ed as a typical and important pathway that plays a role in many physiological functions.…”
Section: Introductionmentioning
confidence: 99%